Factors For Acceptance of Electronic Fiscal Devices by Small and Medium Enterprises in Tanzania - Deogratias Dafi; Felix Joseph Chille (The Institute of Academic Research and Publication (IARP), 2023)
The study aimed to assess factors for the acceptance of Electronic Fiscal Devices by small and medium enterprises in Tanzania. The UTAUT model without moderating factors, such as gender, age, and factors, guided this study. The constructs of perceived trust were added as a theoretical contribution to the study. The study employed the Survey strategy in data collection by administering the questionnaires. A sample of 400 respondents was drawn from the population under the study. Quantitative data were analyzed based on descriptive statistical analysis and multiple linear regression Analysis. The survey strategy was employed, and questionnaires were administered to collect data. The sample consisted of 400 respondents selected from the target population. Quantitative data was collected and analyzed using a multiple linear regression model. The study's findings revealed that performance expectancy and effort expectancy significantly acceptance of electronic Fiscal devices (EFD) among business owners in Tanzania. However, perceived trust was found to not influence acceptance of Electronic Fiscal devices (EFD) among business owners in Tanzania. These results validate the UTAUT model and highlight the significance of performance expectancy and effort expectancy in influencing the acceptance of electronic Fiscal devices (EFD) among business owners in Tanzania. Additionally, the inclusion of perceived trust as a construct in the study model, suggests that tax authorities in Tanzania should explore other determining factors beyond perceived trust to enhance acceptance of electronic Fiscal devices (EFD) among business owners in Tanzania.